Comparison of levobupivacaine alone and in combination with fentanyl and sufentanil in patients undergoing transurethral resection of the prostate - Belgin Akan; Ozgur Yagan; Bora Bilal; Deniz Erdem; Nermin Gogus (Journal of Research in Medical Sciences, 2013)
Background: It was aimed to compare the efficacy and adverse effects of levobupivacaine alone and in combination with fentanyl and sufentanil during transurethral resection of the prostate (TURP) under spinal anesthesia. Materials and Methods: In this prospective, randomized, double-blind trial, 60 patients undergoing elective TURP under spinal anesthesia were randomized into three groups. Ten milligrams of 0.5% levobupivacaine in Group-I, 7.5 mg 0.5% levobupivacaine combined with 25 μg fentanyl in Group-II and 7.5 mg 0.5% levobupivacaine with 2.5 μg sufentanil in Group-III were administered intrathecally. Results: The time for sensorial block to reach level T10 was 10.2 ± 2.0, 6.9 ± 1.7 and 7.0 ± 1.4 min in Group-I, II and III, respectively ( P < 0.001). The maximum sensorial block level was T8 in all groups. The frequency of a complete motor block was higher in Group-I. The mean duration of motor block was shorter in Group-II and III than in Group-I ( P < 0.001). There were no differences between groups regarding side effects ( P > 0.05). The time for first analgesic request was shorter in Group-I than in the other two groups ( P < 0.05). During the first postoperative 24-h period, 11 (58%) patients in Group-I, 9 (48%) patients in Group II and 9 (45%) patients in Group-III required an analgesic drug ( P > 0.05). Conclusion: This study showed that combining lower dose levobupivacaine with fentanyl and sufentanil provides faster onset of sensorial block, lower frequency and shorter duration of motor block, and longer analgesia time in TURP under spinal anesthesia.